Phenomenological realism versus scientific realism : Reinhardt Grossmann - David M. Armstrong metaphysical correspondence - Cumpa, Javier; Tegtmeier, Erwin (Philosophische Analyse ;, 2009)
The two eminent metaphysicians Armstrong and Grossmann exchanged letters for ten years in which they discussed crucial points of their respective ontologies. They have a common basis. Both do metaphysics proper and not linguistic philosophy. Both advocate universals and acknowledge the key position of the category of states of affairs. However, they differ on the simplicity of universals and the nature of states of affairs. There is also a fundamental methodological disagreement between them. Armstrong accepts only the evidence of natural science and has a materialist view on mind while Grossm.